The Creed Theory in the Allocation of Inheritance Rights Pertaining to Inherited Property: A Gender Equality Perspective - Wahidah, Wahidah; Ilhami, Adi Wahyu Ilhami (Indonesian Association of Islamic Family Law Lecturers, 2025)
Problem Statement: The inheritance rights of spouses over personal property within an estate represent a complex and frequently contested issue in contemporary legal and social contexts. Although Islamic inheritance law (faraidh) governs these rights, their application in practice is often inconsistent, stemming from assumptions that spouses do not contribute to the acquisition of family wealth. Objective: This study seeks to examine the interpretation of faraidh in the context of principles of gender equality, particularly in cases involving spousal inheritance. Methods: Employing a qualitative normative legal method, this research analyses primary legal materials—specifically Islamic inheritance law and the Compilation of Islamic Law (KHI)—and is supported by secondary sources such as legal journals and empirical findings. Data were collected through literature reviews, in-depth interviews with key informants, and participant observations in inheritance disputes, particularly those involving withheld dowry (mahar). The study utilises the Credo theory and the essence of marriage as analytical frameworks. Results: The findings indicate that spousal inheritance rights, even in short-duration marriages, are valid within the faraidh framework and should not be disregarded. Furthermore, an interpretation of the Qur’anic verse Al-Nisa:12 reveals compatibility between Islamic inheritance law and gender equality. Conclusion: The study concludes that integrating a contextual understanding of marital relationships and gender justice into inheritance practices is essential to prevent discriminatory treatment and to uphold the legal rights of surviving spouses.